Distributions of PAHs, NPAHs, OPAHs, BrPAHs, and ClPAHs in air, bulk deposition, soil, and water in the Shandong Peninsula, China: Urban-rural gradient, interface exchange, and long-range transport - Anan Qi; Pengcheng Wang; Jianhua Lv; Tong Zhao; Qi Huang; Yiming Wang; Xiongfei Zhang; Miao Wang; Yang Xiao; Lingxiao Yang; Yaqin Ji; Wenxing Wang (Ecotoxicology and Environmental Safety, 2023)
A systematic study of the movement of PAHs (Polycyclic aromatic hydrocarbons) and their derivatives through air, soil, and water is key to understanding the exchange and transport mechanisms of these pollutants in the environment and for ultimately improving environmental quality. PAHs and their derivatives, such as nitrated PAHs (NPAHs), oxygenated PAHs (OPAHs), brominated PAHs (BrPAHs) and chlorinated PAHs (ClPAHs), were analyzed in air, bulk deposition, soil, and water samples collected from urban, rural, field, and background sites on the eastern coast of China. The goal was to investigate and discuss their spatiotemporal variations, exchange fluxes, and transport potential. The concentrations of PAHs and their derivatives in the air and bulk deposition displayed distinct seasonal patterns, with higher concentrations observed during the winter and spring and lower concentrations during the summer and autumn. NPAHs exhibited the opposite trend. Significant urban-rural gradients were observed for most of the PAHs and their derivatives. According to the air-soil fugacity calculations, 2–3 ring PAHs, BrPAHs, and ClPAHs were found to volatilize from the soil into the air, while 4–7 ring PAHs, OPAHs, and NPAHs deposited from the air into the soil. The air-water fugacity of the PAHs and their derivatives indicated that surface water was an important source for the ambient atmosphere in Qingdao. The characteristic travel distances (CTDs) and persistence (Pov) for atmospheric transport were much lower than that for the water samples, which may be due to the longer half-lives of PAHs and their derivatives in water. NPAHs and ClPAHs with long transport distances and strong persistence in water could lead to a significant impact on marine pollution.